Development of A We-Based Clinic Information Service System Application Using PHP And MySQL - Ilyas, Abdi; Sasongko, Ananto Tri; Nugroho, Agung (Riwayat: Educational Journal of History and Humanities, 2025)
This research, titled "DEVELOPMENT OF A WEB-BASED CLINIC INFORMATION SERVICE SYSTEM APPLICATION USING PHP AND MySQL" aims to optimize efficiency and service quality at Atlantic Clinic through the implementation of a web-based information system. Analysis and testing indicate that the current conventional service method is no longer adequate, leading to inefficiencies in service processes. The newly designed system enhances administrative efficiency by accelerating patient data recording and retrieval. Additionally, the queue system provides better time estimates for patients, while the medical record system ensures the security and accuracy of patient data. The integrated cashier system improves payment transaction efficiency, reducing billing errors. Master data management, which includes medication, medical procedures, doctors, and users, becomes more structured and accurate. The implementation of this system is expected to bring significant improvements to the quality of service at Atlantic Clinic, making it more modern, effective, and efficient.